Section 4 - Screening [ P 43-48 ] Drug Discovery and Pharmaceutical (Acta Pharmacologica Sinica; Vol 34, No 1 (July 2013): Vol 34, Supplement 1 (July 2013): Acta Pharmacologica Sinica, 2017)
Section 4